1998
DOI: 10.1038/sj.onc.1202054
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 E7 protein sensitizes cervical keratinocytes to apoptosis and release of interleukin-1α

Abstract: Interleukin-1a (IL-1a) is a multifunctional cytokine that promotes in¯ammation, tissue remodeling and epithelial hyperplasia. Keratinocytes produce and sequester large amounts of biologically active IL-1a which can be released after injury or infection. We show that high level expression of human papillomavirus (HPV) type 16 E6 and E7 oncoproteins enhanced release of IL-1a from cultures of normal cervical keratinocytes (relative eectiveness E74E6/E7>E64 control). The amount of IL-1a released was directly relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
1
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 30 publications
0
43
1
4
Order By: Relevance
“…Considering the role of the individual viral oncoproteins, it is known that E7 can stimulate cells to undergo programmed cell death. 52,53 E6 counteracts this process by neutralizing the apoptosis-inducing function of p53. 4 However, CD95 resistance of HPV16 ϩ malignant cells cannot be exclusively attributed to a direct inhibitory effect of the viral E6 oncoprotein on the cell death execution machinery since no correlation between the levels of p53 and the commitment to undergo apoptosis was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the role of the individual viral oncoproteins, it is known that E7 can stimulate cells to undergo programmed cell death. 52,53 E6 counteracts this process by neutralizing the apoptosis-inducing function of p53. 4 However, CD95 resistance of HPV16 ϩ malignant cells cannot be exclusively attributed to a direct inhibitory effect of the viral E6 oncoprotein on the cell death execution machinery since no correlation between the levels of p53 and the commitment to undergo apoptosis was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in serum-deprived MEF pRb 7/7 , apoptosis was The DNA fragmentation, characteristic of the internucleosomal cleavage that occurs during apoptosis, was analysed on a 1.8% agarose gel. DNA was extracted from NIH3T3 cells expressing di erent E7 genes as described in Materials and methods Figure 4a, apoptosis was also induced by TNFa/cycloheximide treatment, which has been shown to promote apoptosis in primary human keratinocytes expressing HPV16 E7 gene (Iglesias et al, 1998). HPV16 E7 protein sensitizes MEF pRb +/+ to apoptosis upon TNFa/cycloheximide treatment, whilst in MEF pRb 7/7 cells the percentage of apoptotic cells was similar in absence or presence of E7 protein (Figure 4b).…”
Section: Prb Inactivation Is An Essential Requirement For Hpv16 E7-inmentioning
confidence: 99%
“…As other stimulators of proliferation, the HPV16 E7 protein, besides the ability to deregulate the cell cycle, promotes apoptosis (Pan andGriep, 1994, 1995;White et al, 1994;Puthenveettil et al, 1996;Iglesias et al, 1998;Stoppler et al, 1998). Expression of HPV16 E7 in normal human ®broblasts (NHF) or in human keratinocytes results in a cytocidal response, which is much more evident in the absence of mitogenic signals and displays the typical features of apoptosis .…”
Section: Introductionmentioning
confidence: 99%
“…The opposing effects of BPV-1 E6 and E7 may be implicated in the life cycle, replication, and maintenance of BPV-1. Recent studies have shown that the high-risk HPV-16 E6 and E7 oncogenes either increase or decrease apoptosis depending on the cell lines and apoptotic stimuli employed (Puthenveettil et al, 1996;Jones et al, 1997;Iglesias et al, 1998;Magal et al, 1998;Rapp and Chen, 1998;Stoppler et al, 1998;Alfandari et al, 1999;Liu et al, 2000b;Mannhardt et al, 2000;Finzer et al, 2002). Interestingly, while normal human diploid fibroblasts that express HPV-16 E7 are highly predisposed to undergo apoptosis in response to growth factor deprivation, they have decreased propensity to undergo apoptosis in response to TNF-and Fas treatment (Jones et al, 1997;Thompson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%